Preparation and characterization of anti-HIV nanodrug targeted to microfold cell of gut-associated lymphoid tissue - Roy, Upal (Int J Nanomedicine, 2015)
The human immunodeficiency virus 1 (HIV-1) still remains one of the leading life-threatening diseases in the world. The introduction of highly active antiretroviral therapy has significantly reduced disease morbidity and mortality. However, most of the drugs have variable penetrance into viral reservoir sites, including gut-associated lymphoid tissue (GALT). Being the largest lymphoid organ, GALT plays a key role in early HIV infection and host–pathogen interaction. Many different treatment options have been proposed to eradicate the virus from GALT. However, it becomes difficult to deliver traditional drugs to the GALT because of its complex physiology. In this regard, we developed a polymer-based Pluronic nanocarrier containing anti-HIV drug called efavirenz (EFV) targeting Microfold cells (M-cells) in the GALT. M-cells are specialized epithelial cells that are predominantly present in the GALT. In this work, we have exploited this paracellular transport property of M-cells for targeted delivery of Pluronic nanocarrier tagged EFV, bioconjugated with anti-M-cell-specific antibodies to the GALT (nanodrug). Preliminary characterization showed that the nanodrug (EFV-F12-COOH) is of 140 nm size with 0.3 polydispersion index, and the zeta potential of the particles was −19.38±2.2 mV. Further, drug dissolution study has shown a significantly improved sustained release over free drugs. Binding potential of nanodrug with M-cell was also confirmed with fluorescence microscopy and in vitro uptake and release studies. The anti-HIV activity of the nanodrug was also significantly higher compared to that of free drug. This novel formulation was able to show sustained release of EFV and inhibit the HIV-1 infection in the GALT compared to the free drug. The present study has potential for our in vivo targeted nanodrug delivery system by combining traditional enteric-coated capsule technique via oral administration.